The Use of Short Video Clips in Improving Students' Listening Skills in Identifying Specific Information at STKIP Muhammadiyah Aceh Barat Daya - Shakila Alka Dwivahmi; Zuhri Efendi (PT PUSTAKA CENDEKIA GROUP, 2026)
Listening is an essential skill in English language learning, yet many EFL learners experience difficulties in understanding spoken English and identifying specific information. This study aimed to investigate the use of short video clips in improving students’ listening skills in identifying specific information at STKIP Muhammadiyah Aceh Barat Daya. This study employed a quantitative approach with a quasi-experimental pre-test and post-test control group design. The participants consisted of 30 students from the sixth and eighth semesters of the English Education Department, who were divided into an experimental group and a control group. The experimental group received listening instruction using four short video clips, while the control group received conventional listening instruction. Data were collected through a 20-item multiple-choice listening comprehension test and analyzed using descriptive statistics and independent-samples t-tests. The results showed that the mean score of the experimental group increased from 44.33 in the pre-test to 73.33 in the post-test, while the control group increased from 26.67 to 52.33. The independent-samples t-test showed a significance value of 0.000, which was lower than 0.05, indicating a statistically significant difference between the post-test scores of the two groups. Therefore, the findings demonstrate that the use of short video clips significantly improved students’ listening skills in identifying specific information. The study suggests that short video clips can serve as an effective and engaging audiovisual medium for supporting listening instruction in EFL classrooms.